2019
DOI: 10.1002/ehf2.12506
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental factors on heart failure decompensations

Abstract: Aims Heart failure (HF) is a clinical syndrome caused by a structural and/or functional cardiac abnormality, resulting in a reduced cardiac output and/or elevated intracardiac pressures at rest or during stress. This disease often causes decompensations, which may lead to hospital admissions, deteriorating patients' quality of life and causing an increment on the healthcare cost. Environmental exposure is an important but underappreciated risk factor contributing to the development and severity of cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
29

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 15 publications
1
10
0
29
Order By: Relevance
“…In European warm period (from June to October), there are significant less admissions than that in the cold period (from December to March). Air temperature is the most significant environmental factor related to heart failure hospital admissions, showing an inversed correlation[ 93 , 94 ]. Heart failure admissions peaked when temperature was between 0 and -10°C[ 68 ].…”
Section: Weather and Other Cardiovascular Disease Beyond Chdmentioning
confidence: 99%
See 1 more Smart Citation
“…In European warm period (from June to October), there are significant less admissions than that in the cold period (from December to March). Air temperature is the most significant environmental factor related to heart failure hospital admissions, showing an inversed correlation[ 93 , 94 ]. Heart failure admissions peaked when temperature was between 0 and -10°C[ 68 ].…”
Section: Weather and Other Cardiovascular Disease Beyond Chdmentioning
confidence: 99%
“…Every 1°C decrease in mean temperature and every 1hPa decrease in air pressure were associated, respectively, with an increase in the daily number of emergency admissions for heart failure by 7.83% (95%CI: 2.06-13.25) and 3.56% (95%CI: 1.09-5.96)[ 71 ]. Some other features, such as precipitation, are also relevant[ 94 ].…”
Section: Weather and Other Cardiovascular Disease Beyond Chdmentioning
confidence: 99%
“…Previous studies have also described a similar trend of increased HF admissions during the winter season. 1 , 17 , 18 , 19 Our study population had shown a peaking of HF admissions among across all range of EF i.e. both for group I and group II.…”
Section: Discussionmentioning
confidence: 66%
“…El hogar, como espacio habitable que brinda condiciones para suplir algunas necesidades, puede, por el contrario, entorpecer el cumplimiento de las mismas. El estado de las viviendas, considerando elementos como las bajas temperaturas, la humedad y la contaminación intradomiciliaria por el uso de combustibles de mala calidad, han sido vinculado con enfermedades respiratorias (Annesi-Maesano & Lundbäck, 2014;Bernstein, 2008;Bornehag, 2001;Douglas, Thomson & Gaughan, 2003;Fisk, Lei-Gomez & Mendell, 2007;Kim, Jahan & Kabir, 2013;Taske, 2005; todos citados en Mould & Baker, 2017), circulatorias y cardíacas (Bean & Mills, 1938;Collins, 1986;citados en Kwong & Jang, 2017;Collins, 1993, citado en O'Sullivan, Howden-Chapman & Fougere, 2011Escolar et al, 2019;Rose, 1996;The Eurowinter Group, 1997), y reumáticas (Shortt & Rugkasa, 2007, citado en O'Sullivan et al, 2011Zeng, Bengtsson, Klareskog & Alfredsson, 2017). Las temperaturas altas, por su parte, se vinculan a ataques cardíacos (Bouchama, 2002, citado en Ormandy & Ezratty, 2016) y al aumento de mortalidad durante olas de calor, siendo las personas mayores de 75 años las más vulnerables (Wolf, Adger & Lorenzoni, 2010).…”
Section: Salud En El Hogarunclassified